Reconstructive Therapy in Patients with Peri-Implantitis in a University Dental Hospital: A Preliminary Retrospective Case Series Focusing on Complications - Ahmad Alahmari; Xavier Costa-Berenguer; Rui Figueiredo; Eduard Valmaseda-Castellón; Alba Sánchez-Torres; Marta García-García (Applied Sciences, 2025)
Peri-implantitis is an inflammatory disease-causing bone loss around dental implants, often requiring reconstructive surgical therapies to reduce probing depth and regenerate bone. However, such surgeries are frequently complicated by postoperative issues. This retrospective case series aimed to identify the main postoperative complications following the reconstructive treatment of peri-implant bone defects in peri-implantitis patients. Data from 14 patients with 21 affected implants were analyzed, including demographics, oral hygiene, surgical techniques, and complications such as wound dehiscence, membrane exposure, and infections. Wound dehiscence was measured using Image J® software version 1.54. Descriptive and bivariate analyses were performed. The results showed that 11 implants (52.4%; 95% confidence interval (95%CI): 29% to 76%) in nine patients (57.1%; 95%CI = 27% to 87%) developed soft tissue dehiscence after one week, with membrane exposure observed in 4 implants. Dehiscence was significantly associated with mandibular implant location (p = 0.003), poor interproximal hygiene (p = 0.008), and membrane exposure (p = 0.034). No postoperative infections were recorded. In conclusion, more than half of peri-implantitis patients undergoing reconstructive surgery experience wound dehiscence, particularly in cases involving mandible, poor hygiene, and membrane exposure. This complication might compromise bone regeneration and reduce the treatment success rate. These results should be interpreted cautiously due to study design limitations (retrospective design, lack of a control group, and small sample size).